PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK TERPADU DENGAN MODEL PROBLEM BASED LEARNING - Arista, Tiara Mala; Mansurdin, Mansurdin; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The research is aimed to describe the improvement of the student’s learning outcomes in learning the Integreted Thematic Subject by using the Problenm-Based Learning Model (PBL) at 5th grade of using both qualitative and quantitative approaches. The subject of the research were the the teacher and 20 student of the school (11 male students, and 9 female student). This research wass conducted in two cycles where each cycle consists of planning, acting, observing dan reflecting. The results of the research is the improvement of student’ learning outcome in learning the Integrated Thematic Subject by using the problem-based-learning outcome is learning the Integrated Thematic Subject by using the Problem-Based-Learning Model at 5th grade of SDN 04 Simalanggang, Payakumbuh.   KEYWORDS : Learning Outcome, Integrated Thematic Learning, Problem- Based Learning Model